Testing dependence between growth and needle litterfall in Scots pine--a case study in northern Finland - Lehtonen, Aleksi; Lindholm, Markus; Hokkanen, Tatu; Salminen, Hannu; Jalkanen, Risto (Tree Physiology, 2008)
Both drought and fungal disease increase needle litterfall of Scots pine ( Pinus sylvestris L.) trees, but most factors causing annual variation in needle litterfall are poorly understood. We hypothesized that radial growth and weather conditions favorable to growth correlate positively with needle litterfall with a lag equal to the number of needle cohorts (here being 5–6). We studied the time series of needle litterfall, stem increment, pollen cone litter and daily weather conditions in a Scots pine stand over 43 years (1961–2004). The cross-correlations of standardized time series were estimated with various lags. Model predictions of annual needle litterfall were tested against independent data. Changes in annual growth and needle litterfall correlated with lags of 0 and 4 years. The best predictors for needle litterfall were May to mid July temperature sum with a lag of 4 years, May rainfall with a lag of 2 years and September temperature with a lag of 6 years. Pollen cone litter correlated negatively with needle litterfall with a lag of 2 years. The study provided empirical evidence that needle litterfall of Scots pine in northern Finland is influenced by needle production and needle mass development that occurred 4 to 6 years earlier.